Churg-Strauss Syndrome or Eosinophilic Granulomatosis with Polyangiitis: Exuberant Classic Clinical Picture of a Rare Disease - Luana Vieira Mukamal; Celso Tavares Sodré; Lara Beatriz Prata; Fernanda Nakasato; Tullia Cuzzi; Marcia Ramos- (Karger Publishers, 2018)
The authors present a classic case of Churg-Strauss syndrome with an exuberant clinical picture in a 34-year-old woman. She showed the following diagnostic criteria: asthma, polyneuropathy, rhinopathy, marked eosinophilia, positive p-ANCA with a perinuclear pattern, and skin histopathology results suggestive of vasculitis with eosinophils. There was a good response to prednisone, dexamethasone pulse therapy, and cyclophosphamide.